2017
DOI: 10.1038/ncomms15652
|View full text |Cite
|
Sign up to set email alerts
|

Sox5 regulates beta-cell phenotype and is reduced in type 2 diabetes

Abstract: Type 2 diabetes (T2D) is characterized by insulin resistance and impaired insulin secretion, but the mechanisms underlying insulin secretion failure are not completely understood. Here, we show that a set of co-expressed genes, which is enriched for genes with islet-selective open chromatin, is associated with T2D. These genes are perturbed in T2D and have a similar expression pattern to that of dedifferentiated islets. We identify Sox5 as a regulator of the module. Sox5 knockdown induces gene expression chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 57 publications
4
19
1
1
Order By: Relevance
“…Previous studies have demonstrated that the HDAC inhibitor, VPA, increases insulin secretion in vivo (19,20). Consistent with these results, the present study revealed that VPA facilitated the secretion of insulin in two pancreatic β-cell lines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have demonstrated that the HDAC inhibitor, VPA, increases insulin secretion in vivo (19,20). Consistent with these results, the present study revealed that VPA facilitated the secretion of insulin in two pancreatic β-cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…5B). The results therefore suggest that VPA may be a novel therapy for T2D, which is consistent with the results of previous studies (19,20).…”
Section: Sirt5 Protein Expression -----------------------------------supporting
confidence: 92%
“…Intriguingly, dysfunctional β cells from T2D human donors had significantly reduced MYT3 and upregulated stress-gene transcription. This latter point, supported by our RePACT-based single-cell RNAseq, is consistent with results from conventional gene expression analyses, which showed down-regulation of MYT3 (Axelsson et al, 2017) and up-regulation of ATF1, ATF3, Hsp40, 70, 90, and 105 (Bugliani et al, 2013;Gunton et al, 2005;Hartman et al, 2004;Marselli et al, 2010;Segerstolpe et al, 2016).…”
Section: Bidirectional Connections Between Myt Tfs and Stress-responssupporting
confidence: 90%
“…Overall, these results help further understanding of the mechanisms by which ROIT regulates beta cell function. Herein, we found some novel lncRNAs, such as lncRNA-SOX5 and lncRNA-PTPRD by RNA-seq assays, which might play a crucial role in human beta cell function based on previous findings [47,48]. However, whether these lncRNAs are able to regulate mouse beta cell function is unclear.…”
Section: Discussionmentioning
confidence: 90%